A qualitative investigation of experts` practice and coaching strategies to promote soccer-specific competencies in players on a talent pathway - Bergmann, F.; Wachsmuth, S.; O`Connor, D.; Larkin, P.; Dugandzic, D.; Höner, H. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction The development of soccer-specific competencies in aspiring players is a major challenge for coaches working in a talent development context. In support of coaches` efforts, research examining the effectiveness of practice and coaching approaches is valuable to enrich practical knowledge. However, methodological weaknesses and a sparse focus on talent development in past research restrict practical implications thereof [1]. To further improve the empirical knowledge base, the present study aims to investigate the practice and coaching strategies of experts to facilitate soccer-specific competencies in early-adolescent players.